Wave polynomials for solving different types of two-dimensional wave equations - Maciąg, Artur; Wauer, Jörg (Computer Assisted Methods in Engineering and Science, 2005)
The paper demonstrates a specific power series expansion technique used to obtain the approximate solution of the two-dimensional wave equation in some unusual cases. The solution for inhomogeneous wave equation, for more complicated shape geometry of the body, discrete boundary conditions and a membrane whose thickness is not constant is shown. As solving functions (Trefftz functions), so-called wave polynomials are used. Recurrent formulas for the particular solution are obtained. Some examples are included.